2015
DOI: 10.1155/2015/831065
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Electron Spin Resonance Phenomenon in α‐Cr2O3 Nanospheres

Abstract: The photoinduced phenomenon in -Cr 2 O 3 nanoscaled spherical particles was investigated in the temperature range of 150 up to 315 K. An X-band electron-spin resonance spectrometry was employed to probe the magnetic behavior in -Cr 2 O 3 under an IR illumination in the nanosecond regime. The photoinduced effect on both low and high field ESR signals appears above 280 K and is remarkably enhanced just below Néel temperature N . Such a photoinduced ESR phenomenon disappears in a reproducible way in the paramagne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…In view of the potential applications of the synthesized pure Eskolaite α-Cr 2 O 3 , it was shown that they do exhibit superior supercapacitance response in a composite form with graphene (12). Likewise, they display a tunable photo-induced magnetism as demonstrated recently (14,16) and hence the possibility to engineer novel photo-tunable magnetic devices.…”
Section: Chemical Valence States By X-ray Photoelectron Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…In view of the potential applications of the synthesized pure Eskolaite α-Cr 2 O 3 , it was shown that they do exhibit superior supercapacitance response in a composite form with graphene (12). Likewise, they display a tunable photo-induced magnetism as demonstrated recently (14,16) and hence the possibility to engineer novel photo-tunable magnetic devices.…”
Section: Chemical Valence States By X-ray Photoelectron Spectroscopymentioning
confidence: 99%
“…Because of its high chemical stability, α-Cr 2 O 3based catalysts are also of importance for the chemical industry in the preparation of several important commodity chemicals and have also been investigated for their potential as Li cathodes (4)(5)(6)(7)(8)(9)(10). As a result of its high refractive index, it is also finds use in cermets designed for low and medium temperature-selective solar absorbers (11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Due to high chemical stability and catalytic potential, Cr 2 O 3 has gained substantial importance in the chemical industry . It has been used for low‐ and medium‐temperature selective solar absorber due to its high refractive index . Anticancer and antibacterial properties of α‐Cr 2 O 3 are also reported …”
Section: Introductionmentioning
confidence: 99%
“…The resonant absorption of an AF material usually requires frequency in the THz region because of the large exchange field of antiferromagnetic interaction confirming the AF nature of Cr 2 O 3 NRs. At 300 K, a highly intense and distorted ESR spectrum was obtained from CrO 2 NRs, whereas a single line ESR spectrum in the PM field region is the characteristic of Cr 2 O 3 NRs Figure e shows the temperature dependences of the inverse of the doubly integrated area (1/DIA) of ESR spectra from 33 to 250 K. We can see that the FM correlations strengthen with cooling for all samples.…”
Section: Resultsmentioning
confidence: 84%